2000
DOI: 10.1109/comst.2000.5340728
|View full text |Cite
|
Sign up to set email alerts
|

An investigation into HFC MAC protocols: Mechanisms, implementation, and research issues

Abstract: This study comprehensively reviews two HFC MAC protocols: Data-Over-Cable Service Interface Specifications (DOCSIS) and IEEE 802.14a. DOCSIS was approved by the ITU as a standard and is supported by many vendors. However, IEEE 802.14a remains a draft due to the delayed standardization process. After briefly introducing the features of HFC networks, the basic operations and mechanisms of these two MAC protocols are then examined. Both standards view an upstream channel as a stream of minislots and have similar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…However, previous studies have shown that the time delay of this algorithm increases rapidly while significantly reducing the network throughput under a heavy network work load [4], [5]. It has been shown that this problem can be mitigated to a certain extent by adjusting the length of the back-off window [4], [5]. Hence, broadcastingservice data provided by a video server to an IP set-top box can be transmitted using the same route.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, previous studies have shown that the time delay of this algorithm increases rapidly while significantly reducing the network throughput under a heavy network work load [4], [5]. It has been shown that this problem can be mitigated to a certain extent by adjusting the length of the back-off window [4], [5]. Hence, broadcastingservice data provided by a video server to an IP set-top box can be transmitted using the same route.…”
Section: Introductionmentioning
confidence: 99%
“…It utilizes what is known as the Truncated Binary Exponential Backoff (TBEB) algorithm [3], which is similar to that used in the IEEE 802.3 standard. However, previous studies have shown that the time delay of this algorithm increases rapidly while significantly reducing the network throughput under a heavy network work load [4], [5]. It has been shown that this problem can be mitigated to a certain extent by adjusting the length of the back-off window [4], [5].…”
Section: Introductionmentioning
confidence: 99%
“…The DOCSIS 1.0 and 1.1 standard [1] was a result of research and development into the performance implications of various QoS mechanisms [2], [3], [4], [5], [6], [7]. Since these were preliminary, prototyping studies, they were conducted using analytical and/or simulation models.…”
Section: Motivationmentioning
confidence: 99%
“…Issues related to the DOCSIS CATV protocol have been studied over the last few years [4], [5], [6], [11], [14], [15], including service disruption events such as large scale power outages [10], [12], [13]. In case of service disruption the connection between the Head-End (HE) and the subscriber Cable Modem (CM) is terminated.…”
Section: Introductionmentioning
confidence: 99%